USING Rhabditis blumi SUDHAUS AS BIOLOGICAL AGENTS TO CONTROL THE PALP BORER, ARABIAN RHINOCEROS BEETLE, Oryctes agamemnon arabicus - M. Tariq, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to use pathogenicity of entomopathogenic nematodes (EPN) Rhabditis blumi Sudhaus (Nematoda: Rhabditida) against palm borer Arabian Rhinoceros Beetle (ARB), Oryctes agamemnon arabicus was evaluated in the lab. And date palm orchards during 2015 - 2017. In the lab tests, EPN was used against the larvae and adults as a direct spray and as treated food (pieces of fresh tissue of the frond bases) at a rate of 0, 500, 1000, 1500 Infective Juveniles (IJs) per mL of R. blumi. Results indicated that EPN caused 89%, 61% and 25%, 20% mortality when used as a direct spray and as treated food on larvae and adults of ARB, respectively. Results of field experiments showed that injection of 50 mL per palm tree with a concentration of 1500 IJs/mL of R. blumi inflected about 45.5% mortality in ARB larvae infesting the tree. Meanwhile, the Population density of ARB larvae reduced to 45.8%, 59.6% during the first and second year of treated date palm trees by injection method respectively. The results of this investigation illustrate the possibility of using EPN R. blumi as a biocontrol agent for managing borers in date palm orchards under field conditions.